Experimental and FE Investigations of Backfill Cover on Large-Diameter GRP Pipes - AbdulMuttalib I. Said; Yahya Jabbar Hussien; Mohammed Hazim Mohammed; Abbas A. Allawi; Teghreed H. Ibrahim; Ayman El-Zohairy; Ahmed M. Abdelbaset (CivilEng, 2024)
This paper presents experimental investigations on buried Glass Reinforced Plastic (GRP) pipes with a diameter of 1400 mm. The tested pipes were buried in dense, gravelly sand and subjected to traffic loads to study the effects of backfill cover on pipe deflection. The experimental program included tests on three GRP pipes with backfill covers of 100 cm, 75 cm, and 50 cm. The maximum traffic loads applied to the pipe–soil system corresponded to Iraqi Truck Type 3 (AASHTO H type). Vertical deflections of the pipes were monitored during the application of these loads. The experimental results showed that, as the backfill cover increased, the maximum vertical deflection of the pipe decreased. Deflection reductions were 38.0% and 33.3% when the backfill increased from 50 cm to 100 cm and from 50 cm to 75 cm, respectively. A 500 mm compacted backfill cover was found to be sufficient to resist traffic loads, with the vertical deflection percentage remaining below the allowable limit. Additionally, the behavior of the GRP pipes under different traffic load configurations was analyzed using finite element (FE) analysis with Plaxis 3D. The model was validated using field data. The study investigated numerous variables impacting the behavior of embedded pipes, including pipe material, pipe thickness, backfill properties, backfill depth, and the properties of the soil beneath the GRP pipe. The deflections of the steel pipe were lower than those of the GRP pipe when using different thicknesses.